At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Solve each equation and justify each step by using the Properties of Equality. Show all your work.

1. [tex]9 - 2c = -13[/tex]

\begin{tabular}{|l|l|}
\hline
STEPS & JUSTIFICATION \\
\hline
Subtract 9 from both sides: [tex]9 - 2c - 9 = -13 - 9[/tex] & Subtraction Property of Equality \\
\hline
Simplify: [tex]-2c = -22[/tex] & Simplification \\
\hline
Divide both sides by -2: [tex]\frac{-2c}{-2} = \frac{-22}{-2}[/tex] & Division Property of Equality \\
\hline
Simplify: [tex]c = 11[/tex] & Simplification \\
\hline
\end{tabular}


Sagot :

To solve the equation [tex]\(9 - 2c = -13\)[/tex], we will use the Properties of Equality and show each step in detail.

### Step-by-Step Solution:

#### 1. Start with the initial equation:
[tex]\[ 9 - 2c = -13 \][/tex]

#### 2. Subtract 9 from both sides of the equation:
[tex]\[ (9 - 2c) - 9 = -13 - 9 \][/tex]

Justification: Subtraction Property of Equality
Subtracting the same number from both sides of an equation keeps the equation balanced.

Simplifying this step:
[tex]\[ -2c = -22 \][/tex]

#### 3. Divide both sides of the equation by -2:
[tex]\[ \frac{-2c}{-2} = \frac{-22}{-2} \][/tex]

Justification: Division Property of Equality
Dividing both sides of an equation by the same nonzero number keeps the equation balanced.

Simplifying this step:
[tex]\[ c = 11 \][/tex]

### Final Answer:
[tex]\[ c = 11 \][/tex]

This is the solution to the equation [tex]\(9 - 2c = -13\)[/tex].